18F-FDG PET/CT in Isolated Primary Extraskeletal Osteosarcoma. (December 2018) - Parihar, Ashwin Singh; Mittal, Bhagwant Rai; Vadi, Shelvin Kumar; Sood, Apurva; Kumar, Rajender; Goni, Vijay
Abstract : Abstract: Extraskeletal osteosarcoma is a rare, high-grade soft tissue malignancy, accounting for approximately 1% of all soft tissue sarcomas. Despite the histologic resemblance to osteogenic osteosarcoma, it is considered as a distinct entity because of the differences in clinical behavior and response to treatment. Hence, imaging plays a vital role in establishing the nonskeletal origin of the tumor, differentiating it from osteogenic osteosarcoma. We present 18 F-FDG PET/CT findings in a case of isolated primary extraskeletal osteosarcoma confirmed on histopathology.